Determinación del paisaje agrícola que influye en la incidencia de plagas en el cultivo de Chocho en la comunidad de Cachipata provincia de Cotopaxi. - Pachacama Gualotuña, Cristina Elizabeth (2018)
The research was developed in the community of Ninín Cachipata, next to the Saquisilí canton, Cotopaxi province. With the objective of knowing how the agricultural landscape influences on pests incidence in the lupine cultivation. Where a vegetable coverage map was generated using of geo-referenced satellite images; which allowed to characterized the different coverage that exist in the sector. In addition, a field sampling was lead on six plots of lupine producers, through the obtained coverage map and with the helping of aerial photographs taken by an aerial device (DRON), It was related to the incidence of plant abundance in crops. The use of soil and landscaping was determined, based on a classification of plant cover: bare soil (41.6%); forests (29.32%); pasture (5.40%); lupine cultivation (8.94%); corn cultivation (2.74%); potato cultivation (5.35%); infrastructure and roads (6.65%), according to the categories given in the map, it was determined the use of land. where corresponds to the pest dynamics, it was verified that the Barrenador de ápice (Elasnopalpus sp) obtained an incidence of de (89%) and the Barrenador de tallo (Elasnopalpus lignosellus) (78%). It was valuated that the agricultural landscape and the incidence of the lupine pest, is inversely proportional, what is said that, to higher vegetal cover lower pest’s incidence to lower vegetal cover, higher pest’s incidence. Because part of the plant cover serves as a natural repellent to the proliferation of certain pests.